Haematological parameters of Malay patients with coinheritance of Southeast Asian ovalocytosis and thalassaemia haemoglobi-nopathy traits in Klang Valley, Malaysia - Riahi, Shahrzad (2013)
Southeast Asian Ovalocytosis (SAO) and thalassaemia-haemoglobinopathies are com-mon inherited red blood cell (RBC) disorders in Southeast Asian countries. SAO, a RBC membrane defect is clinically asymptomatic. It is characterized by normal RBC parame-ters by in full blood count (FBC) with presences of oval stomatocytic RBCs in peripheral blood film. Thalassaemia-haemoglobinopathy, a globin defect of RBC is one of the ma-jor public health problems in Malaysia. Unlike SAO, thalassaemia-haemoglobinopathies is generally accompanied by hypochromic microcytic RBC parameters. Thalassaemia-haemoglobinopathies screening programme is mainly depends on evaluation of haema-tology (RBC) parameters. Therefore, its evaluations in the presence of those co-inheritance disorders are important to ensure the screening for thalassaemia-haemoglobinopathies is optimum. Objective: To determine the prevalence of co-inheritance of SAO and thalassaemia-haemoglobinopathies in the Malay population and to evaluate the RBC parameters in those patients. Method: Prevalence of co-inheritance of SAO and thalassaemia-haemoglobinopathies was determined by recruit-ing 150 respondents among Malay volunteers’ blood donors in UPM. Their blood sam-ple were analysed for FBC, blood film, Hb analysis and serum ferritin. A total of 132 Ma-lay patients with thalassaemia-haemoglobinopathies, SAO and co-inheritance of both were identified through samples for thalassaemia-haemoglobinopathies screening sent to laboratory haematology, Kuala Lumpur Hospital. These patients were consented and recruited to involve in this study. Their blood samples also were analysed for similar tests as blood donors. The DNA analysis was performed for respondents suspected of alpha thalassaemia (hypochromic microcytic RBC indices with normal serum ferritin and HPLC) and SAO (presence of stomatocytes in blood film). Single–tube multiplex PCR was used for confirmation of α-thalassaemia while PCR carried out to detect SAO. One-way ANOVA test using SPSS version 19 was used to analyse these data where p-value of < 0.05 was considered as statistically significant. Results: Prevalence of thalassae-mia–haemoglobinopathies and SAO among blood donors like Hb E trait, β-thalassaemia trait, α3.7-thalassaemia, α4.2-thalassaemia, αSEA-thalassaemia and SAO were 2.66%, 0.66%, 7.33%, 0.66% and 0.66% and 4.66% respectively. None of these donors was with co-inheritance of SAO and thalassaemia-haemoglobinopathies. All the participants in this study were divided into normal and anaemic groups according to their Hb level. The mean of RBC parameters in co-inheritance of SAO and Hb E such as Hb, MCV, MCH, MCHC, and RDW were 4.5 x106/μL, 10.33 g/dL, 66.33 fl, 22.5 pg, 33.96 g/dL,18.3%, respectively. Among all the RBC indices, the mean MCV were significantly lower in co-inheritance cases as compared to respondents with only Hb E trait alone. The mean of RBC parameters in co-inheritance of SAO and β- thalassaemia trait such as RBC count, Hb, MCV, MCH, MCHC and RDW were of 3.98 x106/μL, 9.41 g/dL, 73 fl, 23.81 pg, 32.68 g/dL, 21.25%, respectively. Among these parameters, the RDW, MCV, and MCH were significantly higher and RBC count was significant lower in co-inheritance cases as compared to respondents with only β-thalassaemia trait alone. Discussion: This study showed respondents with co-inheritance of thalassaemia-haemoglobinpathies and SAO have lower MCV and MCH values as compared to refer-ence standard in thalassaemia screening programme. The difference of the MCV value was significantly lower in co-inheritance of SAO and Hb E trait. The mean MCH in both groups of in co-inheritance was 22.5 pg and 23.8 pg, that has also lower value as com-pared to the references cut–off point, which were, being used for thalassaemia-haemoglobinopathies screening programme in Malaysia. Conclusion: Co-inheritance of SAO and thalassaemia-haemoglobinopathies does not have significant effect on cut-off values of RBC parameters which is, fundamental for thalassaemia-haemoglobinopathies screening.